Reconstruction of Maxillary Defect by Means of Bipedicled Forehead Flap: A Novel Surgical Technical Report - Harshmohan Pathak1, Sobhan Mishra2 , Jayant Kumar Dash3, Sudipta Sahu4 , Kalyan Sundar Pal4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Forehead and temple region of act as tissue reservoir for harvesting flap for reconstruction of the orbital,periorbital and mid-face defect. Depending on requirement different kind of flap can be harvested fromthis region and for this sound knowledge of vascular anatomy of this region is required. Usually largefree flaps are adapted to cover a large maxillectomy deformity. Here, in this case, a bi-pedicled foreheadflap harvested based on frontal and parietal branch of the superficial temporal artery and was used forrehabilitation maxillectomy with external skin deformity